(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the current scientific and practical significance of methods for calculating the concentration of elements (CC), biogeochemical activity of plants (BHA) and biological absorption coefficients (BOD) in various types of soils, biogeochemical studies, as well as in saline soils. In addition, along with the coefficient of biological absorption of trace elements, litho- and pedogeochemical properties of macroelements are illustrated as examples based on tabular data.